Corrigendum on the report ‘The research journal TRANSPORT: peer-reviewing process in 2016’ - Prentkovskis, Olegas; Junevičius, Raimundas (Transport, 2017)
"Corrigendum on the report ‘The research journal TRANSPORT: peer-reviewing process in 2016’." Transport, 32(1), p. 111.